Driving the clean energy transition in Cameroon: A sustainable pathway to meet the Paris climate accord and the power supply/demand gap - Iweh, Chu Donatus; Ayuketah, Yvan Jose Agbor; Gyamfi, Samuel; Tanyi, Emmanuel; Effah-Donyina, Eric; Diawuo, Felix Amankwah (Frontiers in Sustainable Cities, 2023)
The Intergovernmental Panel on Climate Change (IPCC) 2021 report has noted the perceived rise in severe weather phenomena such as heat radiations, hurricanes, flooding, and droughts and the rising scientific evidence attributing these events to anthropogenic sources of climate change. Cameroon as a nation is equally exposed to these climate vulnerabilities, and contributing to global climate efforts is imperative. She has earmarked the integration of 25% renewables in its electricity production mix and a 32% emission reduction, all as part of her commitment to global climate action. The fresh commitments coupled with a rapidly growing power demand have paved the way for a revolutionized approach to electricity generation in Cameroon. However, the imminent changes, as well as their implications, remain uncertain. This study explores how these emission reduction targets can be achieved through the adoption of a more sustainable power transition, which provides realistic solutions for emission reduction, escaping high carbon pathways. The assessment of the level at which long-term electricity generation scenarios in Cameroon could be renewable energy intensive was done using the Low Emissions Analysis Platform (LEAP) tool following a backcasting approach. The study noted that there is an implementation gap between earmarked policy ambitions and existing measures. The study recommended several opportunities in aspects, such as suitable share of technologies, administrative reforms, and required adjustments within the Nationally Determined Contributions (NDCs), which the government could exploit in the electricity sector to sail across the challenging trade-offs needed to become a sustainable economy in a carbon-constrained world. It equally examines actions that could help close the gap between earmarked policy ambitions and existing pathways and proposes cost-effective methods that were identified as priorities.